Deletion of sphingosine 1-phosphate receptor 1 in myeloid cells reduces hepatic inflammatory macrophages and attenuates MASH - Gopanandan Parthasarathy; Nanditha Venkatesan; Guneet Singh Sidhu; Myeong Jun Song; Chieh-Yu Liao; Fanta Barrow; Amy Mauer; Tejasav Sehrawat; Yasuhiko Nakao; P. Vineeth Daniel; Debanjali Dasgupta; Kevin Pavelko; et al. (Hepatology Communications)
Background:. Immune cell–driven inflammation is a key mediator of metabolic dysfunction–associated steatohepatitis (MASH) progression. We have previously demonstrated that pharmacological sphingosine 1-phosphate (S1P) receptor modulation ameliorates MASH and is associated with attenuated accumulation of intrahepatic macrophage and T-cell subsets. Although S1P receptors are expressed on several immune cell types, given the prominent role of monocyte-derived recruited macrophages in the sterile inflammation of MASH, we hypothesized that deletion of S1P receptor 1 (S1P1) on myeloid cells may ameliorate MASH by reducing the accumulation of proinflammatory monocyte-derived macrophages in the liver. Methods:. The LyzMCre approach was used to generate myeloid cell–specific knockout mice, termed S1pr1 MKO . Littermate S1pr1 loxp/loxp mice were used as wild-type controls. MASH was established by feeding mice a high-fat, -fructose, and -cholesterol (FFC) diet for 24 weeks, which led to the development of steatohepatitis and MASH-defining cardiometabolic risk factors. Liver injury and inflammation were determined by histological and gene expression analyses. Intrahepatic leukocyte populations were analyzed by mass cytometry and immunohistochemistry. Results:. Histological examination demonstrated a reduction in liver inflammatory infiltrates and fibrosis in high-fat, -fructose, and -cholesterol–fed S1pr1 MKO compared to wild-type. There was a corresponding reduction in alanine aminotransferase, a sensitive marker for liver injury. As determined by mass cytometry, a significant decrease in recruited macrophages was noted in the livers of high-fat, -fructose, and -cholesterol–fed S1pr1 MKO mice compared to wild-type. Gene ontology pathway analysis revealed significant suppression of the peroxisome proliferator–activated receptor gamma and mitogen-activated protein kinase pathways in S1pr1 MKO consistent with attenuated MASH in mice. Conclusions:. Deletion of S1P1 in myeloid cells is sufficient to attenuate intrahepatic accumulation of monocyte-derived macrophages and ameliorate murine MASH.